Efek Terapi Pemberian Vitamin E Terhadap Kerusakan Histopatologi Ginjal Tikus Putih (Rattus norvegicus) Yang Diinduksi Dexamethasone - Kendok, Padre Pio; Ndaong, Nemay A; Laut, Meity M (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2024)
The purpose of this study was to determine whether or not there was a therapeutic effect of vitamin E administration on dexamethasone-induced kidney histopathological damage of white rats. This study used 20 white rats (Rattus norvegicus) aged 2-3 months with a body weight of 200 grams divided into 5 groups, namely negative control (K) without dexamethasone and vitamin E, positive control group (P0) given dexamethasone subcutaneously at a dose of 0.13 mg / Kg BB, treatment group 1 (P1) given dexamethasone subcutaneously at a dose of 0.13 mg / Kg body weight and vitamin E orally at a dose of 150 mg / Kg body weight, treatment group 2 (P2) given dexamethasone subcutaneously at a dose of 0.13 mg / Kg body weight and vitamin E orally at a dose of 200 mg / Kg body weight, and treatment group 3 (P3) given dexamethasone subcutaneously at a dose of 0.13 mg / Kg body weight and vitamin E orally at a dose of 250 mg / kg body weight. Adaptation is carried out for 7 days. Experimental animals are then terminated and kidney organs are taken to make histopathological preparations with HE staining then the preparations are observed under a microscope. The observed parameter is damage to the glomerulus and proximal tubules of the kidneys. The results showed that dexamethasone was able to damage the kidneys characterized by necrosis of the glomerulus and hydropic degeneration of the proximal tubules of the kidneys shown in the positive control group (P0). In the group given vitamin E, only the P3 group with a dose of vitamin E 250 mg / kg body weight was able to provide a therapeutic effect on damage to the glomerulus and renal tubules due to the toxic effects of dexamethasone.